Strengthening Competitive Advantages to Improve Sales Performance: The Effect of Organizational Strategy and Knowledge Management - Yufita Ernawati; Dwi Ningsih; Nur Wening (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The multilevel marketing industry in Indonesia has shown dynamic growth in line with increased direct sales activities. However, this development has not always been accompanied by stable sales performance, companies face competitive pressures and changing consumer preferences. This situation requires companies to strengthen their internal capabilities in order to improve competitiveness and sales performance. This study aims to analyze the influence of organizational strategy and knowledge management on sales performance through competitive advantage in MLM companies in Surakarta. The study uses a quantitative approach with a census technique on 193 leaders. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that organizational strategy and knowledge management have a positive and significant effect on competitive advantage, and competitive advantage has a positive and significant effect on sales performance. In addition, competitive advantage is proven to mediate the effect of organizational strategy and knowledge management on sales performance. This study contributes to strengthening the knowledge-based view and strategic management perspectives in explaining sales performance achievement through competitive capabilities and provides practical implications for MLM companies in formulating strategies to improve sales performance.